A subject-oriented reference model for Digital Twins - Bönsch, Jakob; Elstermann, Matthes; Kimmig, Andreas; Ovtcharova, Jivka (Computers & industrial engineering, 2022)
The term “Digital Twin” is used in context of a wide range of applications but neither research nor industry have agreed upon one singular definition. Presented here is a novel and formal, subject-oriented reference model for Digital Twin systems that does not focus on technical architectural concepts or particular implementation specific details, but rather on the general possibilities and functionalities that can be expected or missed from Digital Twins. The model depicts the interactions of a Digital Twin system with other entities (i.e. humans, IT-systems and other Digital Twin systems). The purpose of the model is to help practitioners understand and especially communicate about Digital Twins and improve their ability to assess and express their own needs and role in context of designing specific Industry 4.0 use cases accordingly. •Novel, subject-oriented reference model for Digital Twin systems.•No focus on technical architectural concepts or specific implementation details.•Focus on possibilities and functionalities that can be expected or missed for DTs.•Improve practitioners ability to understand and communicate about Digital Twins.•Improve practitioners’ ability to assess and express own needs and role in system.